القيم التقليدية ودورها في مقاومة التحول الرقمي بالمؤسسة دراسة ميدانية على موظفي بلدية الوادي - حليمة قنصر; فتيحة صك (جامعة الوادي - University of Eloued, 2025)
"هدفت الدراسة إلى معرفة أثر القيم التقليدية في تعطيل أو مقاومة التحول الرقمي داخل المؤسسات العمومية الجزائرية، من خلال تحليل العلاقة بين البنية الثقافية التقليدية ومتطلبات الرقمنة الحديثة. اتبعت الدراسة المنهج الوصفي التحليلي، واستُخدم الاستبيان كأداة رئيسية لجمع البيانات. وتمثلت العينة في 60 موظفًا من مختلف الرتب الإدارية داخل بلدية الوادي. توصلت الدراسة إلى أن القيم التقليدية ما تزال تؤثر بشكل ملحوظ على وتيرة التحول الرقمي داخل البلدية، حيث تُفضَّل المعاملات الورقية، وتُسجَّل مقاومة لاستعمال الأدوات التكنولوجية الحديثة، خاصة في ظل ضعف التكوين الرقمي والخوف من التغيير. كما كشفت النتائج عن استعداد جزئي لدى بعض الفئات (الشباب – أصحاب الشهادات) للانخراط في الرقمنة بشرط توفير الدعم المناسب. وقد أوصت الدراسة بضرورة إعداد خطة إدماج ثقافي رقمي تدريجي تأخذ بعين الاعتبار البعد القيمي للمؤسسات الجزائرية. "The study aimed to explore the impact of traditional values on hindering or resisting digital transformation within Algerian public institutions. It analyzed the relationship between traditional cultural structures and the requirements of modern digitization. The study adopted a descriptive and analytical methodology, using a questionnaire as the primary tool for data collection. The sample consisted of 60 employees from various administrative levels in a public institution located in the municipality of El Oued. The findings revealed that traditional values still significantly affect the pace of digital transformation, with a strong preference for paper-based procedures and noticeable resistance to technological tools, especially due to lack of training and fear of change. However, a partial openness to digital adoption was observed among younger and more educated staff, provided appropriate support is ensured. The study recommended the implementation of a gradual digital integration plan that respects and adapts to the value system of Algerian institutions."
مذكرة ماستر قسم علوم الاجتماعية تخصص علم اجتماع تنظيم وعمل.
Keywords: الجزائر; المؤسسات العمومية; الثقافة التنظيمية; التحول الرقمي; القيم التقليدية; Traditional values; Digital transformation; Organizational culture; Public institutions; Algeria.